2009
DOI: 10.1111/j.1600-6143.2009.02574.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Valganciclovir Prophylaxis up to Day 120 in CMV-Seropositive Lung Transplant Recipients

Abstract: Seventy-six cytomegalovirus (CMV)-seropositive lung transplant recipients receiving valganciclovir (900 mg/day) for CMV prophylaxis were compared with a group of 87 patients receiving oral ganciclovir (3000 mg/day). Prophylaxis was administered to day 120 post-transplantation and follow-up was 1 year. In addition, a study was conducted on risk factors for CMV infection/disease. CMV disease incidence was 7.9% and 16.1% for valganciclovir and oral ganciclovir, respectively (p = 0.11). Patients receiving valganci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
2
20
0
1
Order By: Relevance
“…Citations are examples supporting these statements and are not meant to include all references on this topic. Additional references can be found in the comprehensive review by Freeman (5) General indirect effects-elevated risks Bacterial infections (19,134,135) Fungal infection (19,26) Viral infections (summarized in (6)) PTLD (136) Cardiovascular events (137) New-onset diabetes mellitus after transplantation (138,139) Immunosenescence (140) Acute rejection (36,37,134) Mortality (19,134,(141)(142)(143)(144) Transplant-specific indirect effects Chronic allograft nephropathy and/or allograft loss after renal transplant (19,145,146) Accelerated hepatitis C recurrence after liver transplant (147) Hepatic artery thrombosis after liver transplant (144,148,149) Allograft vasculopathy after cardiac transplant (150,151) Bronchiolitis obliterans after lung transplant (37,141,143) hereafter referred to as D+/R−). Preemptive therapy is defined as serial testing done weekly or biweekly for the first few months after transplant or after treatment of rejection, with treatment dose antiviral therapy initiated once a certain defined positive threshold is reached.…”
Section: Universal Prophylaxis and Preemptive Therapymentioning
confidence: 99%
“…Citations are examples supporting these statements and are not meant to include all references on this topic. Additional references can be found in the comprehensive review by Freeman (5) General indirect effects-elevated risks Bacterial infections (19,134,135) Fungal infection (19,26) Viral infections (summarized in (6)) PTLD (136) Cardiovascular events (137) New-onset diabetes mellitus after transplantation (138,139) Immunosenescence (140) Acute rejection (36,37,134) Mortality (19,134,(141)(142)(143)(144) Transplant-specific indirect effects Chronic allograft nephropathy and/or allograft loss after renal transplant (19,145,146) Accelerated hepatitis C recurrence after liver transplant (147) Hepatic artery thrombosis after liver transplant (144,148,149) Allograft vasculopathy after cardiac transplant (150,151) Bronchiolitis obliterans after lung transplant (37,141,143) hereafter referred to as D+/R−). Preemptive therapy is defined as serial testing done weekly or biweekly for the first few months after transplant or after treatment of rejection, with treatment dose antiviral therapy initiated once a certain defined positive threshold is reached.…”
Section: Universal Prophylaxis and Preemptive Therapymentioning
confidence: 99%
“…This ''late-onset CMV disease,'' often defined as disease after the prophylactic period ends, has been associated with increased risk for graft failure after kidney transplantation and increased mortality in liver transplant recipients despite adequate treatment for CMV disease once detected (8,9). Several retrospective reports have also suggested that late-onset disease occurs frequently in lung recipients despite courses of prophylaxis as long as 3-6 months (10,11).…”
mentioning
confidence: 99%
“…Valganciclovir, an oral prodrug that achieves ganciclovir concentrations comparable to those of intravenous (i.v.) ganciclovir (11), is at least as effective and safe in reducing CMV infections after lung transplantation (8,(12)(13)(14)(15)(16)(17)(18). Controversy persists, however, over the recommended duration of valganciclovir prophylaxis.…”
mentioning
confidence: 99%